1986
DOI: 10.1159/000238416
|View full text |Cite
|
Sign up to set email alerts
|

Ceftriaxone Therapy in Otolaryngological and Pulmonary Infections

Abstract: The efficacy of ceftriaxone, 1 g given intramuscularly once daily, was evaluated in 38 patients with pneumonia (n = 11), pulmonary empyema (n = 2), bronchitis (n = 4), tonsillitis (n = 9), sinusitis (n = 7), and otitis (n = 5). Causative organisms were Streptococcus pneumoniae (n = 11), viridans type streptococcus (n = 1), Haemophilus influenzae (n = 6), group A streptococcus (n = 10), Staphylococcus aureus (n = 3), Klebsiella pneumoniae (n = 2), Pseudomonas aeruginosa (n = 1), Escherichia coli (n = 2), Proteu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0
2

Year Published

1987
1987
1995
1995

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 6 publications
0
4
0
2
Order By: Relevance
“…Fraschini et al [7] demonstrated the efficacy of cef triaxone (1 g/day for a mean duration of 7.4 days) in otorhinolaryngological and pulmonary infections. Their study included 38 patients and did not report any failure of ceftriaxone.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fraschini et al [7] demonstrated the efficacy of cef triaxone (1 g/day for a mean duration of 7.4 days) in otorhinolaryngological and pulmonary infections. Their study included 38 patients and did not report any failure of ceftriaxone.…”
Section: Discussionmentioning
confidence: 99%
“…According to Fraschini et al [7], ceftriaxone adminis tered at 1 g/day may be better tolerated than at 2 g/day. This group of investigators observed 2 cases of diarrhea in a series of 38 patients (5.2%) after increasing the daily dose from 1 to 2 g in 1 patient, and after adding ticarcillin (2 g/day) in another patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Die Ofloxacin-Konzentrationen in gynä kologischen Geweben nach einer Gabe von entweder 100 mg 2mal täglich per os während 3 Tagen oder nach 1 maliger Gabe von 200 und 300 mg per os lagen in der gleichen Grössenordung wie die Serumkonzentrationen [4,9,11]. Auch die Norfloxacin-Konzentrationen in der Scheide, der Zervix, den Eileitern und im Ovar übersteigen nach 1 maliger Gabe von 400 mg per os die simultanen Serumkonzentrationen nicht [7], Obwohl die Serumkonzentration von Ofloxacin höher liegt als die von Ciprofloxacin, erreichten beide Substanzen vergleichbare Gewebekonzen trationen, da Ofloxacin im Gegensatz zu Ciprofloxacin eine schwache Gewebepenetration aufweist [1].…”
Section: Diskussionunclassified
“…Die Gewebekonzentrationen von Norfloxacin hingegen werden im Bereich der entsprechenden Serumspiegel angegeben, d.h., das Penetrationsvermö gen von Norfloxacin ins Gewebe ist ebenfalls deutlich geringer als das von Ciprofloxacin [7], …”
Section: Diskussionunclassified